AL-HUQUL AD-DALALIYAH WA MUKAWWINAH AL-MAâ€™NA LI FIâ€™LI â€œTHAHHARAâ€ FI AL-QURâ€™AN - Munjiah, Ma'rifatul; Syafina, Hanna Izzah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
The field of meaning and components is one of the bases for understanding the meaning of a language. And this theory helps researchers uncover the meaning of the verb 'to purify' in Arabic. The verb 'to purify' was chosen because it has an essential meaning for Muslims. Even the Qur'an uses various lexemes for this verb by looking at its context, subject, and function because different lexemes carry different meanings and legal implications. Therefore, this study aims to describe the meaning field, analyze the meaning component, and explain the verbum component of the verb 'to purify' in Arabic. This research is descriptive qualitative research. The data were collected from the Qur'an, with selective reading and note-taking techniques. The data analysis technique uses an interactive model by Miles and Huberman, namely by collecting data from sources and sorting it then selecting it to produce findings of four purifying verbs, namely Ø·ÙŽÙ‡Ù‘ÙŽØ±ÙŽØŒ Ù‚ÙŽØ¯Ù‘ÙŽØ³ÙŽØŒ Ø²ÙŽÙƒÙ‘ÙŽÙ‰ØŒ, and Ø³ÙŽØ¨Ù‘ÙŽØÙŽ. The following components of meaning are determined through the type of subject, object, characteristics of the object, and how it works and concluded that the verb 'to purify' is included in the category of state verb and process verb. The field of meaning and components is one of the bases for understanding the meaning of a language. And this theory helps researchers uncover the meaning of the verb 'to purify' in Arabic. The verb 'to purify' was chosen because it has an essential meaning for Muslims. Even the Qur'an uses various lexemes for this verb by looking at its context, subject, and function because different lexemes carry different meanings and legal implications. Therefore, this study aims to describe the meaning field, analyze the meaning component, and explain the verbum component of the verb 'to purify' in Arabic. This research is descriptive qualitative research. The data were collected from the Qur'an, with selective reading and note-taking techniques. The data analysis technique uses an interactive model by Miles and Huberman, namely by collecting data from sources and sorting it then selecting it to produce findings of four purifying verbs, namely Ø·ÙŽÙ‡Ù‘ÙŽØ±ÙŽØŒ Ù‚ÙŽØ¯Ù‘ÙŽØ³ÙŽØŒ Ø²ÙŽÙƒÙ‘ÙŽÙ‰ØŒ, and Ø³ÙŽØ¨Ù‘ÙŽØÙŽ. The following components of meaning are determined through the type of subject, object, characteristics of the object, and how it works and concluded that the verb 'to purify' is included in the category of state verb and process verb.